MEDIA SOSIAL RAMAH SOSIAL VS HOAX - Reni Juliani (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This study aims to find out how to reduce the dissemination of hoax information and to make social media into social-friendly media so people can anticipte the dissemination of hoax information in various social media and avoid the impacts of the information contained negative contents. A library research method was used in this study. The theory of media dependency is the underlying theory of this study.This theory relates to the effects of media that are considered as information systems that have an important role in people’s lives. Information from such media can have cognitive, affective, and behavioral effects. The results of the studyshowed that the hoax information can be reduced by increasing the media literacy and social media literacy. In addition, the Government of Indonesia has enacted severals laws governing the dissemination of information to ethnic discrimination that is often an issue in the media that causes disunity in the community. These laws include the Law of Electronic Information and Transactions, the Criminal Code, and the Law of the Elimination of Radical and Etnic Discrimination.